A comparison of the wound healing dynamics in an acute and newly developed chronic wound model using Neutral endopeptidase, an inhibitor of Substance P. - Boodhoo, Kiara (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.